Diamond device architectures for UV laser monitoring. (30th June 2016) - Salvatori, S; Girolami, M; Oliva, P; Conte, G; Bolshakov, A; Ralchenko, V; Konov, V
Abstract: The paper reviews the status of diamond detectors for UV laser monitoring and imaging. Single pixel detectors, position sensitive architectures, optically activated switches and sensor arrays for beam positioning and imaging are analyzed. The performances of natural diamond and synthetic diamond produced by chemical vapor deposition are compared to evaluate the suitability of such an outstanding material for the described applications.